Implementation of The Independent Curriculum in Elementary Schools - Koesyono Efendi, Firmansah; I Wayan Suastra (EDUPEDIA Publisher, 2023)
This independent learning curriculum is an independent learning curriculum where teachers and students have the freedom to innovate, the freedom to learn independently and be creative in the process of teaching and learning activities. Curriculum changes are also monitored for various changes, including changes in the learning process and evaluation. the curriculum in schools pays attention to the needs and potential of students through independent learning and the value of the Pancasila student profile. This study used a qualitative type approach to conduct a literature review of various previous studies (literature review). The purpose of writing this article is to analyze various existing theories by looking at comparisons with previous theories. The literature used is research or review existing in scientific papers and has been published in various journals. The implementation of the independent curriculum in elementary schools has been carried out even though it only took representation as an initial implementation trial such as grades 1 and grade 4. The implementation of the new curriculum was carried out in stages, teachers needed training to deepen studies related to the curriculum, PNS teachers and honorary teachers at schools given the opportunity to participate in socialization or workshop by dividing the group into several waves. The implementation of the independent curriculum is a new chapter in all fields of education, starting at the elementary level up to tertiary institutions. The implementation of the new curriculum at the initial stage has not been implemented in its entirety in every class in elementary schools. In general, the implementation of the independent curriculum in elementary schools has been carried out even though it only took representation as an initial stage.